2011
DOI: 10.1590/s0102-311x2011000300020
|View full text |Cite
|
Sign up to set email alerts
|

Canine visceral leishmaniasis in the Krenak indigenous community, Resplendor, Minas Gerais State, Brazil, 2007

Abstract: The authors conducted a cross-sectional study of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…This was not supported however by a Brazilian study of 33,937 dogs (França-Silva et al, 2003 ). No specific canine gender predisposition has been described for ZVL in various endemic countries (Pozio et al, 1981 ; Abranches et al, 1991 ; Sideris et al, 1996 ; Antônio et al, 2007 ); however, in France a greater prevalence of ZVL was found among male dogs (Lanotte et al, 1975 ) and in an endemic area of Brazil high rates of seropositivity were also found among male animals (Mouta-Confort et al, 2010 ).…”
Section: Leishmaniasis In Canidsmentioning
confidence: 99%
“…This was not supported however by a Brazilian study of 33,937 dogs (França-Silva et al, 2003 ). No specific canine gender predisposition has been described for ZVL in various endemic countries (Pozio et al, 1981 ; Abranches et al, 1991 ; Sideris et al, 1996 ; Antônio et al, 2007 ); however, in France a greater prevalence of ZVL was found among male dogs (Lanotte et al, 1975 ) and in an endemic area of Brazil high rates of seropositivity were also found among male animals (Mouta-Confort et al, 2010 ).…”
Section: Leishmaniasis In Canidsmentioning
confidence: 99%
“…Thus, the peridomicile areas in these studies exhibit certain key aspects that exacerbate leishmaniasis exposure: domestic animals as food sources for female sandflies, fruit trees and vegetables as shelter, and organic material for immatures ( 24 ). Another study in the Minas Gerais revealed a 46% overall infection rate in dogs in the Krenak indigenous community ( 27 ). As dogs were mostly asymptomatic (27.3%) and oligosymptomatic (54.5%), such findings may reflect the ineffectiveness of dog culling based on low-sensitivity diagnostic tests as undetected animals remain in the area and maintain the Leishmania cycle ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another study in the Minas Gerais revealed a 46% overall infection rate in dogs in the Krenak indigenous community ( 27 ). As dogs were mostly asymptomatic (27.3%) and oligosymptomatic (54.5%), such findings may reflect the ineffectiveness of dog culling based on low-sensitivity diagnostic tests as undetected animals remain in the area and maintain the Leishmania cycle ( 27 ).…”
Section: Discussionmentioning
confidence: 99%